Overcurrent and Directional Overcurrent Protection for Microgrid - Salsabila, Zahira Shiva; Adrianti, Adrianti; Nasir, Muhammad (LPPM Universitas Andalas, 2023)
Microgrids will become common in future electrical distribution networks. Numerous operating modes that occur in microgrids make the development of protection schemes and settings challenging. This paper aims to develop a simple protection scheme for the Microgrid IEC Benchmark without any expensive equipment such as communication apparatus. The scheme consists of directional and non-directional overcurrent relays with standard inverse characteristics. For the simulation tool, Digsilent powerfactory is employed. Four operating modes of the microgrid are applied to verify the relays’ coordination. The results show that the proposed scheme successfully protects the microgrid during short circuit faults with acceptable time margins.